Preparation method of a struvite fireproof coating for urine wastewater source

CN122978779APending Publication Date: 2026-10-27TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611182181.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0036](一)本发明以尿液为氮磷来源、以富含镁离子的水源或可溶性镁盐为镁源,实现废物的资源化利用,原料来源广泛,成本低廉。尿液收集便捷,尤其适用于源分离厕所、公共厕所等场景,可显著降低废水管网输送和集中处理的综合成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978779A_ABST
    Figure CN122978779A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of fireproof coating preparation, and discloses a preparation method of a urine wastewater source struvite fireproof coating, which comprises the following steps: anaerobically treating urine; injecting the treated urine into a pH adjusting tank to adjust the pH of the urine to alkaline; adding a magnesium ion-rich water source or a soluble magnesium salt to the urine after pH adjustment and stirring to make ammonia nitrogen and phosphate in the urine react with magnesium ions to generate struvite precipitation; performing solid-liquid separation on the obtained struvite precipitation, washing the obtained solid, performing solid-liquid separation again, drying, and grinding to obtain struvite powder; and mixing the struvite powder with a polymer emulsion, ammonium polyphosphate, pentaerythritol or di-pentaerythritol, melamine, a pigment and filler, and water to prepare the fireproof coating. The application promotes the hydrolysis of urea into ammonia nitrogen through anaerobic pretreatment, recovers struvite by taking a soluble magnesium salt or a magnesium ion-rich water source as a magnesium source, and applies the product to fireproof coating, so that the resource utilization and high-value utilization of urine are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fire-retardant coating preparation technology, specifically, it relates to a method for preparing a fire-retardant coating for urinary wastewater source guano. Background Technology

[0002] Urine (such as human urine and livestock urine) contains high concentrations of nutrients such as nitrogen and phosphorus. If discharged directly without treatment, it not only wastes resources but may also lead to eutrophication of water bodies. Traditional urine treatment methods mostly focus on achieving discharge standards, failing to achieve effective recovery and utilization of nitrogen and phosphorus resources.

[0003] Struvite (magnesium ammonium phosphate, MgNH4PO4·6H2O) precipitation is a recognized technology for the simultaneous recovery of nitrogen and phosphorus. By adding a magnesium source to nitrogen- and phosphorus-containing wastewater, struvite precipitates are formed under alkaline conditions, simultaneously removing nitrogen and phosphorus. The product can be used as a slow-release fertilizer or industrial raw material. However, existing struvite recovery technologies mostly use chemically pure magnesium salts as the magnesium source, resulting in high raw material costs. Furthermore, urea in urine, in its fresh state, has not yet been hydrolyzed into ammonia nitrogen, leading to low efficiency when directly used for struvite precipitation. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a method for preparing a fire-retardant coating for urine wastewater source struvite. The method involves promoting the hydrolysis of urea into ammonia nitrogen through anaerobic pretreatment, then recovering struvite using soluble magnesium salts or magnesium-rich water as the magnesium source, and finally applying the product to the fire-retardant coating, thereby realizing the resource utilization and high-value utilization of urine.

[0005] Based on the above-mentioned objectives, the technical solution of this invention is as follows:

[0006] This invention provides a method for preparing a fire-retardant coating for urinary wastewater sources made from struvite, comprising:

[0007] (1) Anaerobic treatment of urine;

[0008] (2) Inject the anaerobic urine into the pH adjustment tank and add alkaline solution to adjust the pH to alkaline;

[0009] (3) After pH adjustment, the urine flows into the nitrogen and phosphorus resource recovery tank, and water rich in magnesium ions or soluble magnesium salts are added and stirred, so that the ammonia nitrogen and phosphate in the urine react with magnesium ions to form struvite precipitate.

[0010] (4) The obtained struvite precipitate was subjected to solid-liquid separation. The obtained solid was washed, and then subjected to solid-liquid separation, drying and grinding to obtain struvite powder.

[0011] (5) The obtained struvite powder is mixed with polymer emulsion, ammonium polyphosphate, pentaerythritol or dipentaerythritol, melamine, pigments and fillers and water to prepare fireproof coating; wherein, by weight, the amount of each component is: 18-25 parts of polymer emulsion, 23-35 parts of ammonium polyphosphate, 6-12 parts of struvite powder, 8-12 parts of pentaerythritol or dipentaerythritol, 7-10 parts of melamine, 6-9 parts of pigments and fillers and 14-20 parts of water.

[0012] Preferably, in step (1), the urine is human or animal urine.

[0013] Preferably, in step (1), the anaerobic treatment adopts at least one of the following methods: static anaerobic fermentation, upflow anaerobic sludge bed, internal circulation anaerobic reactor, continuous stirring anaerobic reactor, baffle plate anaerobic reactor, septic tank, and anaerobic pond.

[0014] Preferably, in step (1), anaerobic fermentation is carried out using the inherent microbial community in urine, or anaerobic fermentation is carried out by inoculating anaerobic sludge.

[0015] Preferably, in step (1), the anaerobic treatment temperature is 15-35℃, the anaerobic treatment time is 15-90 days, and the oxidation-reduction potential is -300 to -100 mV.

[0016] More preferably, the anaerobic treatment temperature is 20-30°C and the anaerobic treatment time is 20-60 days; most preferably, the anaerobic treatment temperature is 25°C and the anaerobic treatment time is 30 days.

[0017] Preferably, in step (2), the alkaline solution is at least one of sodium hydroxide solution, potassium hydroxide solution, and sodium carbonate solution.

[0018] Preferably, in step (2), the pH is adjusted to be alkaline in the range of 9 to 11.

[0019] Preferably, in step (2), stirring is continued during pH adjustment.

[0020] Preferably, in step (3), before adding water rich in magnesium ions or soluble magnesium salts, the molar ratio of ammonia nitrogen to inorganic phosphorus in the urine is 2 to 12.

[0021] Preferably, in step (3), the molar ratio of magnesium ions to inorganic phosphorus in urine is 1 to 2.

[0022] More preferably, the molar ratio of magnesium ions to inorganic phosphorus in urine is 1.2 to 2.0; most preferably, the molar ratio of magnesium ions to inorganic phosphorus in urine is 1.4:1.

[0023] Preferably, in step (3), the magnesium-rich water source is at least one of seawater, salt lake brine, and underground brine.

[0024] Preferably, in step (3), the soluble magnesium salt is at least one of magnesium chloride hexahydrate, magnesium sulfate heptahydrate, anhydrous magnesium sulfate, magnesium chloride, and magnesium oxide.

[0025] Preferably, in step (3), the stirring is performed using a magnetic stirrer or an electric stirrer, with a stirring time of 5 to 30 minutes and a stirring speed of 100 to 300 rpm.

[0026] Preferably, in step (4), the solid-liquid separation is carried out by centrifugation or filtration.

[0027] Preferably, in step (4), the centrifugation speed is 2000-8000 r / min and the centrifugation time is 5-10 min.

[0028] Preferably, in step (4), the vacuum degree of the filtration method is 0.02 to 0.09 MPa, and the filter medium is filter paper or microporous filter membrane with a pore size of 0.45 to 5 μm.

[0029] Preferably, in step (4), the washing process involves rinsing with pure water 4 to 8 times.

[0030] Preferably, in step (4), the drying temperature is 25-40°C.

[0031] Preferably, in step (4), the average particle size of the guano powder obtained after grinding is 15-35 μm.

[0032] Preferably, in step (5), the polymer emulsion is selected from at least one of vinyl acetate-ethylene copolymer emulsion, acrylic emulsion, styrene-acrylic emulsion, pure acrylic emulsion, silicone-acrylic emulsion, and styrene-butadiene emulsion.

[0033] Preferably, in step (5), the ammonium polyphosphate is selected from at least one of type I ammonium polyphosphate, type II ammonium polyphosphate, melamine-modified ammonium polyphosphate, and pentaerythritol-modified ammonium polyphosphate.

[0034] Preferably, in step (5), the pigment or filler is at least one of titanium dioxide, zinc oxide, barium sulfate, talc, calcium carbonate, kaolin, and wollastonite.

[0035] The beneficial effects of this invention are:

[0036] (i) This invention utilizes urine as a source of nitrogen and phosphorus, and water rich in magnesium ions or soluble magnesium salts as a magnesium source, to achieve resource utilization of waste. The raw materials are widely available and inexpensive. Urine collection is convenient, making it particularly suitable for scenarios such as source-separated toilets and public toilets, and can significantly reduce the overall cost of wastewater pipeline transportation and centralized treatment.

[0037] (II) This invention promotes the hydrolysis of urea into ammonia nitrogen through anaerobic pretreatment, thereby improving the raw material utilization rate of the subsequent struvite reaction, with a phosphorus removal rate of over 97%. The effective combination of anaerobic pretreatment and struvite precipitation streamlines the entire process from urine collection and stabilization to nitrogen and phosphorus resource recovery.

[0038] (III) The urine-based struvite powder recovered in this invention can partially replace ammonium polyphosphate in fire-retardant coatings, reducing the coating formulation's dependence on commercial APP and lowering the raw material cost of the coating. In high-temperature flame continuous burning tests, the temperature on the back side of the coating containing urine-based struvite exhibits a unique dynamic change characteristic: it first rises to a peak temperature, then gradually decreases and tends to stabilize. The final stable temperature is basically the same as that of the pure ammonium polyphosphate system, significantly improving the load-bearing capacity of the weights. The carbon layer's ability to resist flame erosion and mechanical damage is significantly enhanced, effectively reducing the risk of premature failure of the carbon layer in a fire. In addition, the introduction of struvite does not adversely affect the coating's application performance and storage stability. Existing coating preparation processes can be directly used without additional modifications to production equipment, facilitating industrial transformation and promotion.

[0039] (iv) The process conditions of this invention are mild. Anaerobic pretreatment can be carried out at room temperature, and struvite crystallization can be completed under alkaline conditions. No high-temperature and high-pressure equipment is required, making the operation simple and easy to scale up. The process parameters can be flexibly adjusted according to the measured water quality of urine from different sources, making it widely applicable. Anaerobic pretreatment can also be flexibly combined with other urine treatment processes, exhibiting good industrial adaptability. Attached Figure Description

[0040] Figure 1 This is a flowchart illustrating the preparation method of the urinary wastewater source struvite fire-retardant coating of the present invention.

[0041] Figure 2 This is a photograph of the actual combustion test bench.

[0042] Figure 3 A photograph of the actual temperature testing instrument;

[0043] Figure 4 Photos of the actual temperature testing points;

[0044] Figure 5 The graph shows the effect of pH on the removal rate of crystalline phosphorus from struvite in Example 1.

[0045] Figure 6The graph shows the effect of the Mg / P molar ratio on the phosphorus removal rate in Example 2.

[0046] Figure 7 The graph shows the effect of the N / P molar ratio on the phosphorus removal rate in Example 3.

[0047] Figure 8 The graph shows the effect of stirring time on phosphorus removal rate in Example 4.

[0048] Figure 9 This is a comparison of the temperature rise curves of formulation 1 and formulation 2 in Example 6;

[0049] Figure 10 This is a photograph of the actual weights used in Example 6. Detailed Implementation

[0050] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention. Unless otherwise stated, the raw materials used in the following embodiments are all commercially available industrial-grade products or chemically pure reagents.

[0051] like Figure 1 As shown, the preparation method of a guano-based fire-retardant coating for urine wastewater sources according to the present invention includes the following steps:

[0052] Urine sources and anaerobic pretreatment:

[0053] The urine processed in this invention is derived from human or animal urine. After collection, if the urine contains a high concentration of suspended solids or organic impurities, it can be pretreated by natural sedimentation or filtration to remove the suspended solids. Anaerobic treatment employs at least one of the following methods: static anaerobic fermentation, upflow anaerobic sludge bed, internal circulation anaerobic reactor, continuous stirred anaerobic reactor, baffle plate anaerobic reactor, septic tank, or anaerobic pond. The urine is anaerobic fermented in a closed or semi-closed reactor using the inherent microbial community in the urine, or by inoculating with anaerobic sludge. The anaerobic treatment temperature is 15–35°C, preferably 20–30°C, and most preferably 25°C. The anaerobic treatment time is 15–90 days, preferably 20–60 days, and most preferably 30 days. During the anaerobic treatment, the oxidation-reduction potential (ORP) is controlled between -300 and -100 mV.

[0054] Under anaerobic conditions, urea in urine is hydrolyzed into ammonia nitrogen by urease, significantly increasing the ammonia nitrogen concentration. Simultaneously, some organic matter is degraded, providing sufficient ammonium ions for the subsequent struvite crystallization reaction. When the ORP is above -100 mV, anaerobic processes are incomplete, urea hydrolysis is insufficient, and the yield of struvite is affected.

[0055] Depending on the actual urine quality, the NH4 content in the urine can be adjusted by adding inorganic salts such as NH4Cl and KH2PO4. + -N and PO4 3- -P concentration, to meet the nitrogen-phosphorus molar ratio requirements for the struvite crystallization reaction.

[0056] Alkali selection and pH adjustment:

[0057] The alkaline solution used to adjust the pH of urine can be sodium hydroxide solution, potassium hydroxide solution, or sodium carbonate solution. Sodium hydroxide solution is highly alkaline and requires a small amount, making it suitable for processes with high pH adjustment precision requirements. Potassium hydroxide solution is comparable to sodium hydroxide solution in effectiveness. Sodium carbonate solution is relatively mildly alkaline, suitable for process systems sensitive to pH fluctuations, and the carbonate ions can react with calcium ions in urine to form calcium carbonate precipitate, reducing the interference of calcium ions on struvite crystallization to some extent. The pH adjustment range is 9–11, preferably 9.5–10.5, and most preferably 10.0. Continuous stirring is required during pH adjustment to ensure thorough mixing of the alkaline solution and urine.

[0058] Magnesium source selection and dosage control:

[0059] The magnesium source can be a soluble magnesium salt or a water source rich in magnesium ions. Soluble magnesium salts are selected from at least one of magnesium chloride hexahydrate, magnesium sulfate heptahydrate, anhydrous magnesium sulfate, magnesium chloride, and magnesium oxide, with magnesium chloride hexahydrate being preferred. Water sources rich in magnesium ions are selected from at least one of seawater, salt lake brine, and underground brine. Seawater is taken from nearshore waters and undergoes sedimentation or filtration to remove suspended impurities before use; salt lake brine and underground brine can be used directly after simple filtration.

[0060] Before adding a magnesium source, the molar ratio (N / P) of ammonia nitrogen to inorganic phosphorus in urine should be controlled between 2 and 12, preferably 6. The added magnesium source contains Mg... 2+ The amount of magnesium source and the molar ratio (Mg / P) of inorganic phosphorus in urine are controlled at 1-2, preferably 1.4. After adding the magnesium source, continuous stirring is performed to reduce the NH4+ in the urine. + PO4 3- With Mg 2+ The reaction proceeds through full contact, producing struvite precipitate.

[0061] Precipitation separation and product processing

[0062] After the reaction, the resulting precipitate mixture is subjected to solid-liquid separation. Solid-liquid separation can be performed by centrifugation or vacuum filtration. Centrifugation is simple to operate and suitable for laboratory and small-scale production, with a centrifugation speed of 2000–8000 r / min and a centrifugation time of 5–10 min. Vacuum filtration is suitable for continuous operation, with a vacuum degree of 0.02–0.09 MPa. Filter paper or microporous membranes with a pore size of 0.45–5 μm can be used as the filter medium. Both methods can be used individually or in combination. The separated solid is washed repeatedly with pure water 4–8 times to thoroughly remove soluble salt impurities. After a second solid-liquid separation, the solid product is dried at 25–40℃ to constant weight and ground to an average particle size of 15–35 μm to obtain the urine-based struvite powder product. Low-temperature drying prevents struvite from losing its water of crystallization and maintains the integrity of its molecular structure.

[0063] Formulation of fire-retardant coatings

[0064] The urine-based struvite powder prepared above is mixed with polymer emulsion, ammonium polyphosphate, pentaerythritol or dipentaerythritol, melamine, pigments and fillers, and water in a certain proportion and stirred evenly to obtain an intumescent fire-retardant coating. The polymer emulsion can be selected from one or more of vinyl acetate-ethylene copolymer emulsion, acrylic emulsion, styrene-acrylic emulsion, pure acrylic emulsion, silicone-acrylic emulsion, and styrene-butadiene emulsion. The ammonium polyphosphate can be selected from one or more of type I ammonium polyphosphate, type II ammonium polyphosphate, melamine-modified ammonium polyphosphate, and pentaerythritol-modified ammonium polyphosphate. The pigments and fillers can be selected from one or more of titanium dioxide, zinc oxide, barium sulfate, talc, calcium carbonate, kaolin, and wollastonite. The pigments and fillers expand upon exposure to fire, providing skeletal support and enhancing the mechanical strength and integrity of the carbon layer. The proportions of each component by mass are as follows: 18-25 parts polymer emulsion, 23-35 parts ammonium polyphosphate, 6-12 parts struvite powder, 8-12 parts pentaerythritol or dipentaerythritol, 7-10 parts melamine, 6-9 parts pigments and fillers, and 14-20 parts water, with a total of 100 parts.

[0065] After the fire-retardant coating is prepared, the coating preparation and curing process includes:

[0066] The prepared fire-retardant coating is evenly applied to the surface of the steel plate after rust removal and cleaning. The coating can be applied by scraping, brushing, or spraying, with a thickness controlled between 1 and 3 mm. After coating, the specimen is placed at room temperature for natural curing and drying for 3 to 7 days to allow the coating to fully harden.

[0067] Example 1: Investigating the effect of pH on the removal rate of crystalline phosphorus from struvite

[0068] Simulated high-phosphorus wastewater was prepared using septic tank supernatant as a substrate to fix NH4. +-N initial concentration 110 mg / L, PO4 3- The initial P concentration was 52.2 mg / L, the Mg / P molar ratio was 1.4:1, and the stirring time was 20 min. The pH of the system was adjusted to 8.0, 9.0, 9.5, 10.0, 10.5, and 11.0 with NaOH solution, respectively. MgCl2·6H2O was added to provide a magnesium source, and the reaction was carried out at 25℃ and 200 rpm for 20 min. After the reaction, the supernatant was filtered through a 0.45 μm filter membrane, and the PO4 content was determined. 3- -P concentration and removal rate were calculated, results are shown in Figure 5 .

[0069] Depend on Figure 5 It can be seen that the phosphorus removal rate first increases and then decreases with increasing pH. The removal rate is only 5.41% at pH=8.0, rises to 87.35% at pH=9.0, reaches 92.53% at pH=10.0, and peaks at 92.69% at pH=10.5. Further increasing the pH to 11.0 reduces the removal rate to 81.66%. These results indicate that the suitable pH range for struvite crystallization is 9.5–10.5, with pH=10.0 being the preferred value.

[0070] Example 2: Investigating the effect of Mg / P molar ratio on phosphorus removal rate

[0071] Under the conditions of pH=10.0, N / P molar ratio of 4.67:1, and stirring time of 20 min, the Mg / P molar ratio was adjusted to 1.0, 1.2, 1.4, 1.6, and 1.8 by changing the amount of MgCl2·6H2O added. The remaining operations were the same as in Example 1, and the results are shown in [Figure 1]. Figure 6 .

[0072] Depend on Figure 6 It can be seen that the phosphorus removal rate increases rapidly with the increase of the Mg / P molar ratio, and then tends to level off. The removal rate is 87.50% when Mg / P=1.0, rises to 92.53% when Mg / P=1.4, and reaches 94.36% when Mg / P=1.8. Considering both the phosphorus removal rate and the cost of the reagents, the range of the Mg / P molar ratio is 1~2, with Mg / P=1.4 being the preferred value.

[0073] Example 3: Investigating the effect of N / P molar ratio on phosphorus removal rate

[0074] Under conditions of pH=10.0, Mg / P molar ratio of 1.4:1, and stirring time of 20 min, the N / P molar ratio was adjusted to 3.4:1, 4.67:1, 6.0:1, 8.0:1, 10.0:1, and 12.0:1 by varying the NH4Cl dosage. The remaining operations were the same as in Example 1. The results are shown in [Figure 1]. Figure 7 .

[0075] Depend on Figure 7 It can be seen that the phosphorus removal rate increases continuously with the increase of the N / P molar ratio, and then gradually slows down. The removal rate reaches 95.21% when N / P = 6.0:1, and further increases to 96.74% when N / P = 12.0:1, but the increase slows significantly. Although the lowest experimental N / P ratio was 3.4:1, according to the principle of chemical equilibrium, a reduction of N / P to 2 is sufficient to drive the formation of struvite precipitate. Under these conditions, although the phosphorus removal rate is lower than the optimal conditions, the precipitate formed is still struvite. After washing, drying, and grinding, the phase composition and microstructure of the struvite powder obtained do not undergo fundamental changes. It can still play a synergistic role in char formation and skeletal support in fire-retardant coatings, and its carbon layer enhancement effect remains usable. Therefore, considering both product availability and reagent cost, the range of the N / P molar ratio is determined to be 2–12, with N / P = 6.0:1 being the preferred value.

[0076] Example 4: Investigating the effect of stirring time on phosphorus removal rate

[0077] Under conditions of pH=10.0, Mg / P molar ratio 1.4:1, and N / P molar ratio 6.0:1, the stirring time was controlled at 5, 10, 20, and 30 min, respectively, with the remaining operations the same as in Example 1. The results are shown in [Figure 1]. Figure 8 .

[0078] Depend on Figure 8 It can be seen that the removal rate is 51.29% after stirring for 5 minutes, jumps to 92.08% after 10 minutes, reaches 94.65% after 20 minutes, and is 95.12% after 30 minutes. Considering both removal efficiency and energy consumption, the stirring time range is 5 to 30 minutes, with 20 minutes being the preferred stirring time.

[0079] Example 5: Anaerobic treatment of urine and preparation of struvite

[0080] Fresh human urine was collected, placed in a sealed glass container, and allowed to ferment anaerobically at 25°C for 30 days. After anaerobic treatment, the NH4 content in the urine was measured. + -N concentration was 670 mg / L, PO4 3- -P concentration was 180 mg / L, Mg 2+The concentration was 48 mg / L. After adjusting the pH of the system to 10.0 with sodium hydroxide solution, magnesium chloride hexahydrate (MgCl2·6H2O) was added at a Mg:P molar ratio of 1.4:1. The mixture was stirred continuously at 200 rpm for 20 min at 25℃, followed by sedimentation. The precipitate was then separated by centrifugation at 4000 r / min for 8 min. The separated solid was washed three times with pure water to thoroughly remove soluble salt impurities. After a second centrifugation, the solid product was vacuum dried at 40℃ to constant weight and ground to an average particle size of approximately 25 μm to obtain urine-based struvite powder. Testing showed that the phosphorus removal rate under these conditions reached 97.89%.

[0081] Example 6: Preparation and Performance Comparison Test of Urine-Based Strombolith Fire-Retardant Coating

[0082] This embodiment sets up two formulations to compare the thermal insulation performance and carbon layer mechanical strength of intumescent fire retardant coatings with and without the addition of urine-based struvite.

[0083] Formula 1 (Comparative Example, Stromboli-Free System): 7.24 g (22.9 parts) of vinyl acetate-ethylene copolymer emulsion (VAE emulsion), 10.26 g (32.4 parts) of ammonium polyphosphate (Type II, degree of polymerization ≥1000), 3.26 g (10.3 parts) of dipentaerythritol, 3.02 g (9.5 parts) of melamine, 2.72 g (8.6 parts) of rutile titanium dioxide, and 5.18 g (16.3 parts) of deionized water were uniformly mixed to obtain a fire-retardant coating. The fire-retardant coating was evenly applied to a 10 cm × 10 cm steel plate surface that had undergone rust removal and cleaning. The coating thickness was approximately 3 mm. The plate was then naturally cured and dried at room temperature for 5 days to obtain a coating sample.

[0084] Formula 2 (Example of the present invention, urine-based struvite system): 8.02 g (22.1 parts) of VAE emulsion, 8.73 g (24.1 parts) of ammonium polyphosphate (Type II, degree of polymerization ≥1000), 3.91 g (10.8 parts) of urine-based struvite powder prepared in Example 5, 3.26 g (9.0 parts) of dipentaerythritol, 3.02 g (8.3 parts) of melamine, 2.72 g (7.5 parts) of rutile titanium dioxide, and 6.60 g (18.2 parts) of deionized water were uniformly mixed to obtain a fire-retardant coating. The coating application and curing methods are the same as in Formula 1. The fire resistance performance test was conducted in an atmospheric environment, using a methane flame as the combustion source. The combustion test bench was constructed as follows... Figure 2 As shown, the temperature testing instrument is as follows Figure 3 As shown, thermocouple thermometers are used to record the temperature changes on the back of the steel plate in real time. The temperature measurement points are as follows: Figure 4As shown, the thermocouple test point is fixed at the center of the back of the steel plate to ensure accurate collection of the highest temperature on the back of the coating.

[0085] Fire resistance performance tests were conducted on the two groups of coating samples. The test conditions were: the coating surface was continuously burned with a 1200℃ methane flame for 20 minutes, while thermocouples were used to record the temperature change at the center of the back of the steel plate. The test results are shown below. Figure 9 Test results show that the coating back temperature of Formula 1 (guano-free) remained stable at 204℃; the coating back temperature of Formula 2 (urine-based guano) exhibited a dynamic change pattern, first rising to 239℃, then gradually decreasing, and finally stabilizing at 215℃. The final back temperature difference between Formula 2 and Formula 1 was only 11℃, indicating that their thermal insulation performance was essentially the same.

[0086] A static load-bearing test with weights was conducted on the expanded carbon layer formed after combustion to evaluate its mechanical strength. The test method was as follows: After the specimen cooled to room temperature after combustion, a known mass of weight was gently placed on the top center of the expanded carbon layer. The mass of the weight was gradually increased until the carbon layer showed obvious collapse, cracking, or was penetrated by the weight. The cumulative total mass of the weights at this point was recorded, which is the ultimate load-bearing value of the carbon layer. The test results are shown below. Figure 10 Test results show that the carbon layer structure of Formula 1 is loose, and the weight bearing capacity is only 150 g; the carbon layer of Formula 2 is dense and complete, and the weight bearing capacity reaches more than 300 g, which is 100% higher than that of Formula 1.

[0087] The above test results fully demonstrate that struvite powder obtained by anaerobic treatment and using urine as the nitrogen and phosphorus source can significantly improve the mechanical strength and structural integrity of the expanded carbon layer when partially replacing ammonium polyphosphate in intumescent fire-retardant coatings, while maintaining the excellent thermal insulation performance of the coating.

[0088] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many specific modifications under the guidance of the present invention without departing from the spirit and scope of the claims, and these modifications all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a fire-retardant coating for urinary wastewater sourced from guano, characterized in that, include: (1) Anaerobic treatment of urine; (2) Inject the anaerobic urine into the pH adjustment tank and add alkaline solution to adjust the pH to alkaline; (3) After pH adjustment, the urine flows into the nitrogen and phosphorus resource recovery tank, and water rich in magnesium ions or soluble magnesium salts are added and stirred, so that the ammonia nitrogen and phosphate in the urine react with magnesium ions to form struvite precipitate. (4) The obtained struvite precipitate was subjected to solid-liquid separation. The obtained solid was washed, and then subjected to solid-liquid separation, drying and grinding to obtain struvite powder. (5) The obtained struvite powder is mixed with polymer emulsion, ammonium polyphosphate, pentaerythritol or dipentaerythritol, melamine, pigments and fillers and water to prepare fireproof coating; wherein, by weight, the amount of each component is: 18-25 parts of polymer emulsion, 23-35 parts of ammonium polyphosphate, 6-12 parts of struvite powder, 8-12 parts of pentaerythritol or dipentaerythritol, 7-10 parts of melamine, 6-9 parts of pigments and fillers and 14-20 parts of water.

2. The preparation method of the guano fire-retardant coating for urine wastewater source according to claim 1, characterized in that, In step (1), the anaerobic treatment adopts at least one of the following methods: static anaerobic fermentation, upflow anaerobic sludge bed, internal circulation anaerobic reactor, continuous stirred anaerobic reactor, baffle plate anaerobic reactor, septic tank, and anaerobic pond; anaerobic fermentation is carried out by utilizing the inherent bacteria in urine or by inoculating anaerobic sludge; the temperature of anaerobic treatment is 15-35℃, the time of anaerobic treatment is 15-90 days, and the oxidation-reduction potential is -300 to -100 mV.

3. The method for preparing the guano fire-retardant coating for urine wastewater sources according to claim 1, characterized in that, In step (2), the alkaline solution is at least one of sodium hydroxide solution, potassium hydroxide solution, and sodium carbonate solution, and the pH is adjusted to an alkaline range of 9 to 11; stirring is continued during the pH adjustment process.

4. The preparation method of the guano fire-retardant coating for urine wastewater source according to claim 1, characterized in that, In step (3), before adding water rich in magnesium ions or soluble magnesium salts, the molar ratio of ammonia nitrogen to inorganic phosphorus in urine is 2 to 12.

5. The method for preparing the guano fire-retardant coating for urine wastewater sources according to claim 1, characterized in that, In step (3), the molar ratio of magnesium ions to inorganic phosphorus in urine is 1 to 2. Stirring is performed using a magnetic stirrer or an electric stirrer for 5 to 30 minutes at a speed of 100 to 200 rpm.

6. The method for preparing the guano fire-retardant coating for urine wastewater sources according to claim 1, characterized in that, In step (3), the water source rich in magnesium ions is at least one of seawater, salt lake brine, and underground brine; the soluble magnesium salt is at least one of magnesium chloride hexahydrate, magnesium sulfate heptahydrate, anhydrous magnesium sulfate, magnesium chloride, and magnesium oxide.

7. The method for preparing the guano fire-retardant coating for urine wastewater sources according to claim 1, characterized in that, In step (4), the solid-liquid separation is carried out by centrifugation or filtration; the centrifugation speed is 2000-8000 r / min and the centrifugation time is 5-10 min; the vacuum degree of the filtration is 0.02-0.09 MPa, the filter medium is filter paper or microporous filter membrane with a pore size of 0.45-5 μm; the washing is carried out by washing with pure water 4-8 times; the drying temperature is 25-40℃; the average particle size of the struvite powder obtained after grinding is 15-35 μm.

8. The method for preparing the guano fire-retardant coating for urine wastewater sources according to claim 1, characterized in that, In step (5), the polymer emulsion is selected from at least one of vinyl acetate-ethylene copolymer emulsion, acrylic emulsion, styrene-acrylic emulsion, pure acrylic emulsion, silicone-acrylic emulsion, and styrene-butadiene emulsion.

9. The method for preparing the guano fire-retardant coating for urine wastewater sources according to claim 1, characterized in that, In step (5), the ammonium polyphosphate is selected from at least one of type I ammonium polyphosphate, type II ammonium polyphosphate, melamine-modified ammonium polyphosphate, and pentaerythritol-modified ammonium polyphosphate.

10. The method for preparing the guano fire-retardant coating for urine wastewater sources according to claim 1, characterized in that, In step (5), the pigments and fillers are at least one of titanium dioxide, zinc oxide, barium sulfate, talc, calcium carbonate, kaolin, and wollastonite.